1993
DOI: 10.1007/bf00012988
|View full text |Cite
|
Sign up to set email alerts
|

The ability of 16 ectomycorrhizal fungi to increase growth and phosphorus uptake of Eucalyptus globulus Labill. and E. diversicolor F. Muell.

Abstract: By contrast, at 4 mg P kg -1 sand growth increases ranged from 0-13 times above that of noninoculated seedlings. P. tinctorius produced the largest growth increase on both eucalypt species. In general, isolates which developed more extensive mycorrhizas on roots produced the largest growth responses to inoculation. Isolates which increased plant growth also increased phosphorus uptake by the plant. Seedlings inoculated with L. laccata and S. verrucosum retained more phosphorus in their roots than plants inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
2
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 18 publications
6
56
2
3
Order By: Relevance
“…Our results are consistent with those of Burgess et al (1993) who studied the effectiveness of 16 fungal isolates in forming ectomycorrhizas with E. globulus and E. diversicolor seedlings and found that only four of them (including P. tinctorius 2144, here referred to as Pisolithus sp.) promoted plant growth and P uptake.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with those of Burgess et al (1993) who studied the effectiveness of 16 fungal isolates in forming ectomycorrhizas with E. globulus and E. diversicolor seedlings and found that only four of them (including P. tinctorius 2144, here referred to as Pisolithus sp.) promoted plant growth and P uptake.…”
Section: Discussionsupporting
confidence: 92%
“…Fungal species have been shown to vary in their capacity to enhance the growth and nutrition of host plants (Bowen, 1973;Huang and Lapeyrie, 1996;Smith and Read, 1997). Among 16 ectomycorrhizal fungi studied by Burgess et al (1993), only four (including Pisolithus sp. in the present study and formerly Pisolithus tinctorius 2144) promoted the growth and P uptake of eucalypt seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, the differences in growth and leaf morphology of I-and NI-seedlings (about 12 to 13% for Ø T , h and LSM, table I, measured after 22 months) may have been too small to be noticed in seedlings less than one year of age or receiving inoculation too recently (see above) and this might be the reason why such effects of mycorrhizae have been reported as dubious in other studies [11].…”
Section: Discussionmentioning
confidence: 71%
“…Even less is known of the influence of the ectomycorrhizal symbiosis on nutrient uptake and allocation [11,13] and water relations [12] of forest trees. For example, ectomycorrhizal symbiosis has been reported to have negative or no effects on root hydraulic conductance (K R ) of Douglas fir seedlings [12].…”
Section: Introductionmentioning
confidence: 99%
“…Esse comportamento pode variar também de acordo com o meio de cultivo utilizado (Hung & Chien, 1978;Ho, 1987). Vários estudos apontam a existência de variação intra e interespecífica entre fungos ectomicorrízicos em relação às características culturais e de crescimento, à colonização da planta hospedeira, à utilização de diferentes fontes de N, entre outras (Gay & Debaud, 1987;Burgess et al, 1993;Oliveira et al, 1994;Rosado et al, 1994b;Burgess et al, 1995b;Kropp, 1997;Sales, 2001;Costa, 2002). As populações monocarióticas apresentam larga variação para essas características resultantes de eventos de recombinação gênica durante a meiose (Rosado et al, 1994a;Kropp, 1997;Sales, 2001;Costa, 2002), constituindo material básico para programas de melhoramento fúngico visando à aplicação no setor florestal.…”
Section: Resultsunclassified